Administração pública: O pacto pela saúde como uma nova estratégia de racionalização das ações e serviços em saúde no Brasil - Fadel, Cristina Berger; Schneider, Luciana; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (FapUNIFESP (SciELO), 2009)
The health pact arises in the Brazilian scene after a number of attempts for the improvement of the Unified Health System (SUS), so as to consolidate social equity. In this perspective, this paper discusses the pact using documental analysis, in order to help the public administration process in Brazil. This new policy, still in the initial phase of implementation, is a unique reality and highly feasible for the improvement of national practices in public health. Its performance is intimately related to overcoming the political barriers inherent to each rank of the administration.
Public administration: The health pact as a new strategy to rationalize healthcare actions and services in Brazil
Keywords: Health policy; Organization & Management; Unified Health System